2011
DOI: 10.1042/bj20110971
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the contributions of the membrane-bound and periplasmic nitrate reductase systems to nitric oxide and nitrous oxide production in Salmonella enterica serovar Typhimurium

Abstract: The production of cytotoxic nitric oxide (NO) and conversion into the neuropharmacological agent and potent greenhouse gas nitrous oxide (N₂O) is linked with anoxic nitrate catabolism by Salmonella enterica serovar Typhimurium. Salmonella can synthesize two types of nitrate reductase: a membrane-bound form (Nar) and a periplasmic form (Nap). Nitrate catabolism was studied under nitrate-rich and nitrate-limited conditions in chemostat cultures following transition from oxic to anoxic conditions. Intracellular N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…The ability of nitrate-ammonifying cells to produce N 2 O in pure culture has been reported before (Bleakley & Tiedje, 1982;Rowley et al, 2012;Stremiń ska et al, 2012). In Salmonella enterica serovar Typhimurium, 20 % of nitrate-N was released as N 2 O under nitrate-sufficient conditions when nitrite had accumulated to millimolar levels (Rowley et al, 2012).…”
Section: Production Of No and N 2 Omentioning
confidence: 88%
See 1 more Smart Citation
“…The ability of nitrate-ammonifying cells to produce N 2 O in pure culture has been reported before (Bleakley & Tiedje, 1982;Rowley et al, 2012;Stremiń ska et al, 2012). In Salmonella enterica serovar Typhimurium, 20 % of nitrate-N was released as N 2 O under nitrate-sufficient conditions when nitrite had accumulated to millimolar levels (Rowley et al, 2012).…”
Section: Production Of No and N 2 Omentioning
confidence: 88%
“…In Salmonella enterica serovar Typhimurium, 20 % of nitrate-N was released as N 2 O under nitrate-sufficient conditions when nitrite had accumulated to millimolar levels (Rowley et al, 2012). This phenotype is envisaged to result from NO production from nitrite by the Nar-type nitrate reductase (see above) and subsequent anoxic NO detoxification to N 2 O.…”
Section: Production Of No and N 2 Omentioning
confidence: 99%
“…It is suggested that if these dedicated NO detoxification systems are unable to lower the NO concentration sufficiently to counteract the ensuing nitrosative stress, FNR will become nitrosylated (30), leading to lowered expression of the nar, nir, nrf, and nap operons (that require [4Fe-4S] FNR for activation) and derepression of hmp expression. We note that NarG is the most important source of endogenously derived NO during nitrate/ nitrite respiration (7,(41)(42)(43). Thus, nitrosylation of FNR would serve to protect the cell by down-regulating the principal source of endogenous NO and by up-regulating Hmp, an important NO-detoxifying enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is an as yet largely unaccounted feature in globalscale models of ammonia production in habitats such as anaerobic soil or marine oxygen minimum zones [29,30,[106][107][108]. The situation is reminiscent to the discovery that bacterial ammonifiers of nitrate and nitrite, i.e., NrfA-containing microorganisms, might significantly contribute to atmospheric N 2 O production, in addition to the denitrifying microbial community [109][110][111][112]. In this case, any NO formed either enzymatically or abiotically from nitrite is apparently detoxified under anaerobic conditions to N 2 O by a variety of NO-reactive enzymes.…”
Section: Environmental Issues and Conclusionmentioning
confidence: 92%